2020
DOI: 10.3390/ma13214871
|View full text |Cite
|
Sign up to set email alerts
|

The Multi-Stage Drawing Process of Zinc-Coated Medium-Carbon Steel Wires in Conventional and Hydrodynamic Dies

Abstract: This paper discusses experimental studies aiming to determine the effect of the drawing method on the lubrication conditions, zinc coating mass and mechanical properties of medium-carbon steel wires. The test material was 5.5 mm-diameter galvanized wire rod which was drawn into 2.2 mm-diameter wire in seven draws at a drawing speed of 5, 10, 15, 20 and 20 m/s, respectively. Conventional and hydrodynamic dies with a working portion angle of α = 5° were used for the drawing process. It has been shown that using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…The greater mass of the pure zinc phase on the drawn wires in the hydrodynamic method causes the production of a greater amount of corrosion products, which insulates and slows down the process. In addition, it should be taken into account that in the hydrodynamic method, the lower residual stresses than in the conventional method (confirmed in earlier work [ 40 ]) do not contribute to the detachment of the insulating layer of white corrosion, which is shown in Figure 11 . The results obtained from the percentage change in the mass of the samples confirmed the greater mass of the samples after two test cycles in the hydrodynamic method, but after cleaning, the greater weight loss was recorded for the conventional method.…”
Section: Corrosion Testsmentioning
confidence: 54%
See 1 more Smart Citation
“…The greater mass of the pure zinc phase on the drawn wires in the hydrodynamic method causes the production of a greater amount of corrosion products, which insulates and slows down the process. In addition, it should be taken into account that in the hydrodynamic method, the lower residual stresses than in the conventional method (confirmed in earlier work [ 40 ]) do not contribute to the detachment of the insulating layer of white corrosion, which is shown in Figure 11 . The results obtained from the percentage change in the mass of the samples confirmed the greater mass of the samples after two test cycles in the hydrodynamic method, but after cleaning, the greater weight loss was recorded for the conventional method.…”
Section: Corrosion Testsmentioning
confidence: 54%
“…The authors’ research published in paper [ 40 ] confirmed the significant influence of the drawing method on wire properties. The results of this work showed that, regardless of the drawing speed, the use of hydrodynamic dies has a positive effect on the drawing process and partially eliminates the negative influence of friction on the flow of the wire surface layer containing the zinc coating.…”
Section: Introductionmentioning
confidence: 87%
“…Muskalski's previous work [7] described and simulated this effect as a phenomenon in which the molecules of lubricant adhere to the wire surface going into the pressure chamber as a thin gap layer between wire and die surfaces. In another recent work, Suliga [8] empirically determined that hydrodynamic lubrication allows to get the optimum tribological conditions at the wire/ die interface leading to obtain better results in the multistage wiredrawing process of medium carbon zinc-coated steel wires.…”
Section: The Role Of Friction In the Wiredrawing Processmentioning
confidence: 99%